Mineralization Process of Biocemented Sand and Impact of Bacteria and Calcium Ions Concentrations on Crystal Morphology - Guobin Xu; Yang Tang; Jijian Lian; Yue Yan; Dengfeng Fu (Advances in Materials Science and Engineering)
Microbial-induced calcite precipitation (MICP) is a sustainable technique used to improve sandy soil. Analysis of the mineralization process, as well as different bacterial suspensions and calcium concentrations on the crystal morphology, revealed that the mineralization process included four stages: self-organised hydrolysis of microorganisms, molecular recognition and interface interaction, growth modulation, and epitaxial growth. By increasing bacterial suspensions and calcium concentrations, the crystal morphology changed from hexahedron to oblique polyhedron to ellipsoid; the best crystal structure occurs at OD600 = 1.0 and [Ca2+] = 0.75 mol/l. It should be noted that interfacial hydrogen bonding is the main force that binds the loose sand particles. These results will help in understanding the mechanism of MICP.